Positive and negative stimuli in relation to tennis players' reaction time - Mead, T. P.; Drowatzky, J. N.; Hardin-Crosby, L. (Perceptual and Motor Skills, 2000)
Research has indicated that negative and positive thoughts may affect sport performance. The purpose of this analogue study was to assess whether negative and positive stimuli influenced tennis performance similar to positive and negative thought. The reaction time (RT) of 40 competitive tennis players was measured during a timed response to a tennis ball rotating in a topspin, sidespin, or backspin direction on the computer screen. Immediately prior to the ball presentation, a phrase (accessory stimulus) was presented visually or aurally. The accessory stimulus provided either positive (e.g., 'nice shot') or negative information (e.g., 'bad shot') followed by the subject's name. Analysis showed a main effect only for the type of spin. The slowest RT occurred when responding to a tennis ball rotating in a backspin direction. A significant interaction was found for the sensory modality (audition vs vision) and polarity (positive vs negative) of the accessory stimulus. RT to negative stimuli was slowest when the accessory stimulus was presented aurally. The quickest RT to positive stimuli occurred when the accessory stimulus was presented aurally. These results indicated that negative and positive stimuli, when presented aurally, affected performance as positive and negative thoughts measured in other studies. Not measured was whether negative and positive stimuli actually produce the negative and positive thoughts, respectively, that have been reported to affect performance.